Differential subnuclear distribution of polyadenylate-rich ribonuclei acid during induction of egg-yolk protein synthesis in male Xenopus liver by oestradiol-17 beta. - Tata, J R (1975)
A 4-8-fold increase in the rate of hepatic nuclear RNA synthesis occurred within 11 h after a single injection of oestradiol-17 beta to male Xenopus to induce egg-yolk protein synthesis. 2. By using a gentle procedure for fractionating nuclei into their major structurally different components [J. R. Tata& B. Baker (1974) Exp. Cell Res. 83. 111-124], it was found that the hormone-induced increase in the total amount of newly made RNA was associated with a 2-10-fold increase in the poly(A) content of nuclear RNA. 3. When the poly (A) content of nuclear RNA was determined by hybridization to poly[3H](U) or specific binding to oligo(dT)-cellulose, most of the increase (10-fold) in poly (A) content of newly synthesized RNA was associated with the euchromatin fractions, whereas the increase was less marked in the other subnuclear fractions. 4. Resolution of nuclear RNA into poly (A)-poor and poly(A)-rich RNA species by chromatography on oligo(dT)-cellulose, followed by polyacrylamide-gel electrophoresis with sodium dodecyl sulphate or in the pressence of 99% formamide, revealed that the hormone caused a preferential enhancement of high-molecular-weight (25S-60S) poly (A)-rich HnRNA (heterogeneous nuclear RNA,) much of which was associated with euchromatin and not with the nuclear sap. 5. Induction of vitellogenin in male frogs was in particular characterized by the appearance of a high-molecular-weight polyadenylated component exhibiting a peak at 35-36S, i.e. a molecular weight of approx. 2.05x10(6)+/-0.15x10(6). Although there is no evidence as yet that such a polyadenylated high-molecular-weight nuclear RNA species contains sequences corresponding to vitellogenin mRNA, it is possible that a high proportion of the most stable form of the putative nuclear precursor to vitellogenin mRNA induced by oestrogen in male Xenopus liver may be only marginally bigger than the cytoplasmic mRNA, and may at any one time be predominantly associated with the euchromatin fraction.